2004
DOI: 10.1074/jbc.m400187200
|View full text |Cite
|
Sign up to set email alerts
|

A Pitfall in Diagnosis of Human Prion Diseases Using Detection of Protease-resistant Prion Protein in Urine

Abstract: Because a definite diagnosis of prion diseases relies on the detection of the abnormal isoform of prion protein (PrP Sc ), it has been urgently necessary to establish a non-invasive diagnostic test to detect PrP Sc in human prion diseases. To evaluate diagnostic usefulness and reliability of the detection of protease-resistant prion protein in urine, we extensively analyzed proteinase K (PK)-resistant proteins in patients affected with prion diseases and control subjects by Western blot, a coupled liquid chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…They also described the pres-ence of protease-sensitive PrP, apparently full-length PrP C , in controls that were free of prion disease, which suggests that normal urine contains PrP C whereas urine from individuals affected with prion disease also contains PrP Sc . However, three subsequent studies using the same antibody failed to detect PrP in urine from normal and prion disease-affected individuals and demonstrated that the false positive results arose from the cross-reaction of anti-mouse IgG with either contaminating bacterial proteins (27) or urinary IgG fragments (28,29). Nonetheless, a series of more recent studies have observed prion infectivity in urine from experimentally and naturally affected animals (30 -33).…”
mentioning
confidence: 99%
“…They also described the pres-ence of protease-sensitive PrP, apparently full-length PrP C , in controls that were free of prion disease, which suggests that normal urine contains PrP C whereas urine from individuals affected with prion disease also contains PrP Sc . However, three subsequent studies using the same antibody failed to detect PrP in urine from normal and prion disease-affected individuals and demonstrated that the false positive results arose from the cross-reaction of anti-mouse IgG with either contaminating bacterial proteins (27) or urinary IgG fragments (28,29). Nonetheless, a series of more recent studies have observed prion infectivity in urine from experimentally and naturally affected animals (30 -33).…”
mentioning
confidence: 99%
“…However, a routine pre-symptomatic test for TSEs would require examination of easily accessible body fluids such as urine, saliva or blood. Although, the presence of PrP Sc -like molecules has been reported in urine of TSE infected animals and humans [24], this report has been questioned by results showing cross-reactivity of anti-PrP antibodies with bacterial proteins present in urine [25]. Because prions were found in the blood of scrapie infected sheep [12], blood seems the best option as a matrix for a non-invasive TSE test for live animals and humans.…”
Section: Analytical Sensitivity With Recombinant Prp Spiked Into Bloomentioning
confidence: 96%
“…For example, Western blots of urine samples used to detect the presence of protease-resistant prion proteins could be misinterpreted. Bands with a molecular mass similar to prion proteins can be detected from these Western blots (96).…”
Section: Sample Matrix Processingmentioning
confidence: 97%